2017
DOI: 10.18632/oncotarget.23464
|View full text |Cite
|
Sign up to set email alerts
|

Computational methods reveal novel functionalities of PIWI-interacting RNAs in human papillomavirus-induced head and neck squamous cell carcinoma

Abstract: Human papillomavirus (HPV) infection is the fastest growing cause of head and neck squamous cell carcinoma (HNSCC) today, but its role in malignant transformation remains unclear. This study aimed to conduct a comprehensive investigation of PIWI-interacting RNA (piRNA) alterations and functionalities in HPV-induced HNSCC. Using 77 RNA-sequencing datasets from TCGA, we examined differential expression of piRNAs between HPV16(+) HNSCC and HPV(–) Normal samples, identifying a panel of 30 HPV-dysregulated piRNAs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Intriguingly the PIWI-piRNA system has been suggested to regulate essential cellular functions of relevance to the repair of somatic tissues, including cell proliferation, viability, cell invasion and migration [22]. However, most of the newly gained knowledge of the functional role of piRNA is based on cancer studies, including studies on skin cancers [23,24] and oral cancers [25][26][27][28]. It is tempting to hypothesize that piRNAs play a role in wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly the PIWI-piRNA system has been suggested to regulate essential cellular functions of relevance to the repair of somatic tissues, including cell proliferation, viability, cell invasion and migration [22]. However, most of the newly gained knowledge of the functional role of piRNA is based on cancer studies, including studies on skin cancers [23,24] and oral cancers [25][26][27][28]. It is tempting to hypothesize that piRNAs play a role in wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 30 piRNAs were dysregulated in HPV16 (+) HNSCC with the protein PIWIL4 and RTL family of retrotransposon-like genes been their potential targets. Three differential expressed piRNAs were further validated in vitro [69]. It was also reported that a collection of 13 piRNAs was found in HNSCC related to smoking.…”
Section: Pirnas In Cancermentioning
confidence: 91%
“…3 A). 20 , 55 , 78 , 79 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 Ectopically expressed piRNAs identified in numerous cancers are shown in Fig. 3 A and Table 1 .…”
Section: Pirnas and Cancer: Cause And Effectmentioning
confidence: 99%
“…4 C). 79 , 84 , 86 , 90 , 100 , 109 Typically, piRNAs target the 3′-untranslated region (3′-UTR) of an mRNA, which may be attributed to the fact that most human genomic piRNAs are derived from 3′-UTR ( Fig. 4 C).…”
Section: Pirnas and Cancer: Cause And Effectmentioning
confidence: 99%